Estimating the quantity of smokeless tobacco consumption among older adults in India - Lucky Singh; Pallavi Sinha; Arpit Singh; Prashant Kumar Singh; Shalini Singh (Elsevier, 2022)
Problem considered: Globally, smokeless tobacco (SLT) users are highest in India. Whilst, studies examined prevalence and determinants of SLT use, no evidence exists which examined the quantity of SLT consumed. Methods: Study utilized national representative data from the Longitudinal Aging Study in India (LASI) which adopted a multistage stratified area probability cluster sampling design. First, we computed the average SLT consumption per day (in grams) from the LASI data. Consecutively, we further utilized the projected population approximations from the 26th round of the official United Nations population estimates and prevalence rate of current SLT use from the Global Adult Tobacco Survey (GATS-2) and LASI Survey, separately to estimate SLT use pattern for the entire Indian population aged 45 or above. Results: The prevalence of current SLT use among older adults was 17.2% wherein the SLT use is higher among men (20.8%). On average, an older adult consumes 1.01 g of SLT on a daily basis. The range of SLT quantity consumed by users' according to the LASI and GATS-2 prevalence, varies from 65,000 kg to 85,000 kg per day whereas, annual consumption ranges from 23 million kilograms to 32 million kilograms, respectively. Conclusion: The development of SLT cessation services examining the quantitative aspects of SLT use would be beneficial in tackling the high SLT burden in India and improving the rates of intention to quit.